Endogenous hormone concentrations and embryogenic callus development in wheat - Jiménez García, Víctor (2001)
Immature zygotic embryos of two wheat (Triticum aestivum L.) genotypes, known for their different ability to generate embryogenic callus, were used as initial explants to establish callus cultures. Embryogenic and non-embryogenic calluses were obtained from the competent genotype (`Combi'), while only non-embryogenic callus was produced by the incompetent one (`Devon'). The morphogenetic competence of each callus type was evaluated by transferring some segments to regeneration conditions. The endogenous hormone concentrations (free indole-3-acetic acid [IAA], abscisic acid [ABA], gibberellins 1, 3 and 20 [GAs], zeatin/zeatin riboside [Z/ZR] and N6[Δ2-isopentenyl] adenine/ N6[Δ2-isopentenyl] adenosine; [iP/iPA]) of the initial explants were determined by means of radio-immunoassay and showed that the only difference was the higher concentration of ABA found in the embryos of the most competent genotype; whose embryos showed a reduced rate of precocious germination. When analysing the endogenous hormone concentrations in the various callus types generated in each genotype, it was found that only differences in the free IAA concentrations were associated with variations in the morphogenic properties of the calluses. Higher concentrations of endogenous free IAA were typical of embryogenic callus cultures. It was also observed that a loss in the embryogenic competence of the calluses, due to a prolonged time of culture, occurred concomitantly with a reduction in free IAA concentrations, practically to the concentrations found in the non-embryogenic calluses.